2012
DOI: 10.3329/jsr.v4i2.7670
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin E on Haematological Parameters in Albino Rats Treated with Gasoline

Abstract: This study was carried out to ascertain the antioxidant properties of vitamin E on haematoxicity caused by gasoline in albino rats using the haemoglobin and white cell count as indices. Thirty-five rats fed diet containing 1000iu of vitamin E per 100mg of feed for 2 weeks (to saturation) prior experiment were injected gasoline intraperitoneally while symptoms of toxicity and haematological parameters were monitored. The result showed that feeding on vitamin E diet increased the haemoglobin concentration while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
(7 reference statements)
2
5
0
Order By: Relevance
“…Antioxidants are the type of molecules that nullify harmful free radicals, produced through a series of reactions ( Joseph et al., 2009 ; George and Adegoke, 2011 , 2012 ; Tanko et al., 2013 ), that are detrimental to living cells, spoil foods, damage materials such as rubber, gasoline, and lubricating oil. Antioxidants terminate these series of reactions through the elimination of free radical intermediates and inhibiting other oxidation reactions ( Sies, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antioxidants are the type of molecules that nullify harmful free radicals, produced through a series of reactions ( Joseph et al., 2009 ; George and Adegoke, 2011 , 2012 ; Tanko et al., 2013 ), that are detrimental to living cells, spoil foods, damage materials such as rubber, gasoline, and lubricating oil. Antioxidants terminate these series of reactions through the elimination of free radical intermediates and inhibiting other oxidation reactions ( Sies, 1997 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the administration of 10 mg AA/kg bw reduced the WBC counts significantly in the rats compared with the control group. This finding suggests that AA (an antioxidant) might be capable of preventing excessive production of WBC ( Liu, 1995 ; George and Adegoke, 2012 ). The significant increase in WBC count in 10 mg SB/kg bw group compared with the control group indicated that SB was recognized as a foreign entity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin E has been shown to ameliorate hemolysis of red blood cells 24. A study by George and Adoke suggested that gasoline induced hemolysis of red blood cells in albino rats could be prevented by feeding them vitamin E rich diet showing the antioxidant property of this vitamin against hemotoxicity 26. Role of vitamin E as an erythrocyte forming factor was demonstrated in a study by Gogu et al in a murine model 27.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, treatment with vitamin E showed a significant increase in hemoglobin (Hb) content only in (500 mg/kg) treated group and after 45 days recovery, while non-significantly decreased in (1000 and 2000 mg/kg) treated groups for 90 days of treatment and after 45 days recovery in the comparison with control group. The increase in Hb content after treatment with the lowest dose of vitamin E (500 mg/kg) might be due to its antioxidant effects (George and Adegoke, 2012). A study by Abdo et al (1986) revealed that treatment with a high dose of vitamin E (2000 mg/kg) for 13 weeks caused a decrease in hematocrit values and Hb concentrations.…”
Section: Discussionmentioning
confidence: 99%